Influence of ionizing treatment on the quality of stored strawberries - Giuggioli, Nicole Roberta; Briano, Rossella; Peano, Cristiana (Progress in Nutrition, 2017)
The use of sustainable sanitization technique such as those of the ionization represent a good opportunity to the management of the post harvest of fresh and perishable fruits of short shelf life such as strawberry and more so if the application of these technologies does not influence significantly the evolution of the qualitative and nutraceutical aspects of the fruits. The aim of this work was to evaluate the effects of a ionizing treatment (T1) (Fruit Control Equipments, Italy) used for the environmental sanitization of the rooms storage (1±1°C) on fresh strawberries. Two everberaing cultivars of strawberry (cv. Portola and Murano) were considered about the evolution of the most rapresentative physical –chemical traits of fruits (weight losses (%), the skin colour, the total soluble solids content (SSC), the pulp firmness, the titratable acidity) and nutraceutical compounds (the total anthocyanin and phenolic contents and the antioxidant activity). The fruits were compared with untreated strawberries (control) stored in normal atmosphere (A.N.) and they were monitored after 3, 6, 9, 13 and 15 days (1±1°C and 95% RH). Both cultivars show their limit of marketability due the weight losses at 9 days. Fruits of cv. Murano show an high quality profile and the consumer acceptance seems to be related to treated samples with ions.